SOCIO-PSYCHOLOGICAL ASPECTS OF COMMUNICATION - F. Tillabaeva; S. Zhabbarova (International Engineering Journal For Research & Development, 2020)
The article discusses the socio-psychological aspects of communication. The socio-psychological interpretation of the modern approach to the concept of "communication" is given